1968
DOI: 10.1002/pol.1968.160060305
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic properties of polybutadienes—linear and lightly crosslinked near the gel point

Abstract: SynopsisViscoelastic properties of four linear and three very lightly crosslinked polybutadienes (microstructure about 50% trans) were studied. Of the latter, two had not reached the gel point, and their molecular weight distributions were determined by sedimentation velocity analysis; the third was crosslinked just past the gel point, with only 32% gel fraction present.Complex shear compliances were measured over a frequency range from 0.1 to 1000 cps at temperatures from -70 to 30°C. with a Fitagerald transd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
1

Year Published

1972
1972
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 21 publications
2
17
1
Order By: Relevance
“…The results demonstrate that the retardation spectra from the bulk response are independent of crosslink density, indicating the local nature of the underlying molecular motions. Also, shown in Figure 10 are the retardation spectra from the shear responses measured at atmospheric pressure, which show a narrowing with increasing crosslink density, consistent with the literature 17–20. To compare the bulk and shear retardation spectra, we first note that the bulk measurements were carried out at ∼67 MPa rather than at atmospheric pressure, leading to a suppression of the retardation spectrum (a decrease in the absolute magnitude) for the bulk response relative to the shear response at short times.…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…The results demonstrate that the retardation spectra from the bulk response are independent of crosslink density, indicating the local nature of the underlying molecular motions. Also, shown in Figure 10 are the retardation spectra from the shear responses measured at atmospheric pressure, which show a narrowing with increasing crosslink density, consistent with the literature 17–20. To compare the bulk and shear retardation spectra, we first note that the bulk measurements were carried out at ∼67 MPa rather than at atmospheric pressure, leading to a suppression of the retardation spectrum (a decrease in the absolute magnitude) for the bulk response relative to the shear response at short times.…”
Section: Resultssupporting
confidence: 78%
“…Moreover, the retardation spectra for the bulk response are independent of crosslink density. Previous studies17–21 indicated that crosslink density influences the viscoelastic properties only at long times, as can be observed in the shear retardation spectrum which narrows with increasing crosslink density. However, because the long‐time mechanisms are unavailable for the bulk response, this behavior cannot be observed for the bulk.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…These values are consistent with literature data reported, for example, by Paul and DiBenedetto [30,31] for a pure cis-1,4-PB system (a p ¼ 6.7 Â 10 À4 K À1 at T ¼ 298 K), by Smith et al [32] for a random PB copolymer sample through 13 C NMR experiments and MD simulations (a p ¼ 7.1 Â 10 À4 K À1 at T ¼ 353 K), by Barlow [28] (a p ¼ 7.35 Â 10 À4 K À1 in the temperature range 277-328 K) and by Valentine et al [33] (a p ¼ 7.5 Â 10 À4 K À1 ) for a random copolymer of PB (containing only 43% cis-1,4). Anderson et al [34] have also reported a p for a high cis-1,4-PB sample through NMR measurements (a p ¼ 5.7 Â 10 À4 K À1 at T ¼ 296 K).…”
Section: B Thermodynamic Propertiesmentioning
confidence: 99%
“…This trend can be reversed with significant coupling entanglements of the branches (Ferry 1980). Examples showing J,",B > J,",L in the entangle system can be found in star- (Masuda et al 1971(Masuda et al , 1981Graessley et al 1976;Graessely 1977;Graessley and Roovers 1979;Raju et al 1981;Masuda et al 1984), comb- (Fujimoto et al 1970;Roovers and Graessley 1981) and random-branched polymers (Valentine et al 1968;Jacovic et ul. 1979).…”
Section: Zero-shear Recoverable Compliancementioning
confidence: 99%